5x + y > = -10
y > = -5x - 10
It will be a solid line because ur problem contains an equal sign.
It will be shaded on the side that includes the origin...because when u sub in (0,0), which is the origin, ur inequality is true
C is correct answer.
On C its saids, no irrational number is rational it's statements is false.
Hope it helped you.
-Charlie
Answer: Degree of polynomial (highest degree) =4
Maximum possible terms =9
Number of terms in the product = 5
Step-by-step explanation:
A trinomial is a polynomial with 3 terms.
The given product of trinomial: ![(x^2 + x + 2)(x^2 - 2x + 3)](https://tex.z-dn.net/?f=%28x%5E2%20%2B%20x%20%2B%202%29%28x%5E2%20-%202x%20%2B%203%29)
By using distributive property: a(b+c+d)= ab+ac+ad
![(x^2 + x + 2)(x^2 - 2x + 3)=(x^2 + x + 2) x^2+(x^2 + x + 2) (-2x)+(x^2 + x + 2)(3)\\\\=x^2(x^2)+x(x^2)+2(x^2)+x^2 (-2x)+x (-2x)+2 (-2x)+x^2 (3)+x (3)+2 (3)\\\\\\=x^4+x^3+2x^2-2x^3-2x^2-4x+3x^2+3x+6](https://tex.z-dn.net/?f=%28x%5E2%20%2B%20x%20%2B%202%29%28x%5E2%20-%202x%20%2B%203%29%3D%28x%5E2%20%2B%20x%20%2B%202%29%20x%5E2%2B%28x%5E2%20%2B%20x%20%2B%202%29%20%28-2x%29%2B%28x%5E2%20%2B%20x%20%2B%202%29%283%29%5C%5C%5C%5C%3Dx%5E2%28x%5E2%29%2Bx%28x%5E2%29%2B2%28x%5E2%29%2Bx%5E2%20%28-2x%29%2Bx%20%28-2x%29%2B2%20%28-2x%29%2Bx%5E2%20%283%29%2Bx%20%283%29%2B2%20%283%29%5C%5C%5C%5C%5C%5C%3Dx%5E4%2Bx%5E3%2B2x%5E2-2x%5E3-2x%5E2-4x%2B3x%5E2%2B3x%2B6)
Maximum possible terms =9
Combine like terms
![x^4+x^3-2x^3+3x^2-4x+3x+6\\\\=x^4-x^3+3x^2-x+6](https://tex.z-dn.net/?f=x%5E4%2Bx%5E3-2x%5E3%2B3x%5E2-4x%2B3x%2B6%5C%5C%5C%5C%3Dx%5E4-x%5E3%2B3x%5E2-x%2B6)
Hence, ![\left(x^2\:+\:x\:+\:2\right)\left(x^2\:-\:2x\:+\:3\right)=x^4-x^3+3x^2-x+6](https://tex.z-dn.net/?f=%5Cleft%28x%5E2%5C%3A%2B%5C%3Ax%5C%3A%2B%5C%3A2%5Cright%29%5Cleft%28x%5E2%5C%3A-%5C%3A2x%5C%3A%2B%5C%3A3%5Cright%29%3Dx%5E4-x%5E3%2B3x%5E2-x%2B6)
Degree of polynomial (highest degree) =4
Number of terms = 5
Answer:
and ![-3x-6 \geq -6](https://tex.z-dn.net/?f=-3x-6%20%5Cgeq%20-6)
Step-by-step explanation:
we have
![-33 > -3x-6 \geq -6](https://tex.z-dn.net/?f=-33%20%3E%20-3x-6%20%5Cgeq%20-6)
we know that
Compound inequality can be divided into two inequalities
so
![-33 > -3x-6](https://tex.z-dn.net/?f=-33%20%3E%20-3x-6)
rewrite
![-3x-6 < -33](https://tex.z-dn.net/?f=-3x-6%20%3C%20-33)
and
![-3x-6 \geq -6](https://tex.z-dn.net/?f=-3x-6%20%5Cgeq%20-6)
therefore
An equivalent form of the compound inequality is
and ![-3x-6 \geq -6](https://tex.z-dn.net/?f=-3x-6%20%5Cgeq%20-6)